Empowering Educational Waqf : Development and Prospects for Private Higher Education Institutions - busry lydiawaty; Majid Nurul; Mujahidin Mujahidin (Al-Kharaj: Journal of Islamic Economic and Business, 2021)
This article seeks to reinstate the concept of educational waqf in recognition of student-related financial difficulties, especially during the era of the covid-19 pandemic. Malaysia and Indonesia promote higher education among their muslim communities. However, issues of sustainability in private higher education will require some effort in the related muslim communities for the empowerment of the educational waqf for future generations. These efforts will benefit not just the students, but also the institutions of education themselves to enhance the national civilization of one country. Al-Azhar University is an example of an institution founded on waqf property, and a symbol as the world's primary and most successful Islamic higher education system due to waqf contributions. Higher education facilities are costly to operate since they need the development of permanent infrastructures such as mosques, academic and administrative buildings, dormitories, and libraries. Additionally, both physical infrastructure maintenance and human skill development need considerable financial commitment. As a result of this reality, this article contributes to a better understanding of the role of educational waqf for institutions of higher learning, particularly private universities or colleges as well as the prospects and sustainability of the institutions for the muslim community.